Non-invasive imaging of acute renal allograft rejection in rats using small animal F-FDG-PET. - Stefan Reuter; Uta Schnöckel; Rita Schröter; Otmar Schober; Hermann Pavenstädt; Michael Schäfers; Gert Gabriëls; Eberhard Schlatter (PLoS ONE, 2009)
BACKGROUND: At present, renal grafts are the most common solid organ transplants world-wide. Given the importance of renal transplantation and the limitation of available donor kidneys, detailed analysis of factors that affect transplant survival are important. Despite the introduction of new and effective immunosuppressive drugs, acute cellular graft rejection (AR) is still a major risk for graft survival. Nowadays, AR can only be definitively by renal biopsy. However, biopsies carry a risk of renal transplant injury and loss. Most important, they can not be performed in patients taking anticoagulant drugs. METHODOLOGY/PRINCIPAL FINDINGS: We present a non-invasive, entirely image-based method to assess AR in an allogeneic rat renal transplantation model using small animal positron emission tomography (PET) and (18)F-fluorodeoxyglucose (FDG). 3 h after i.v. injection of 30 MBq FDG into adult uni-nephrectomized, allogeneically transplanted rats, tissue radioactivity of renal parenchyma was assessed in vivo by a small animal PET-scanner (post operative day (POD) 1,2,4, and 7) and post mortem dissection. The mean radioactivity (cps/mm(3) tissue) as well as the percent injected dose (%ID) was compared between graft and native reference kidney. Results were confirmed by histological and autoradiographic analysis. Healthy rats, rats with acute CSA nephrotoxicity, with acute tubular necrosis, and syngeneically transplanted rats served as controls. FDG-uptake was significantly elevated only in allogeneic grafts from POD 1 on when compared to the native kidney (%ID graft POD 1: 0.54+/-0.06; POD 2: 0.58+/-0.12; POD 4: 0.81+/-0.06; POD 7: 0.77+/-0.1; CTR: 0.22+/-0.01, n = 3-28). Renal FDG-uptake in vivo correlated with the results obtained by micro-autoradiography and the degree of inflammatory infiltrates observed in histology. CONCLUSIONS/SIGNIFICANCE: We propose that graft FDG-PET imaging is a new option to non-invasively, specifically, early detect, and follow-up acute renal rejection. This method is potentially useful to improve post-transplant rejection monitoring.